Future mobility development in passenger transport - Melichar, Vlastimil; Salava, Daniel; Chmelař, Martin (Univerzita Pardubice, 2006)
This article describes basic factors of development and modelling of future mobility in passenger transport. Mobility development models are constrained by two basic factors, which represent travel time budget and travel money budget. Model and scenario of total mobility development is function of fixed travel money budget and travel time budget. By creation of model and future mobility development scenario in particular transport modes, we work on determination of particular transport mode shares and on four constraining factors. These factors are fixed travel time budget, path dependence, urban land-use patterns and balancing equation of total traffic volume. By model construction we examine at first two budget constraints of passenger – travel time budget and travel money budget, that are core elements of model methods. In further sequence we estimate future demand for services, that are offered by state, it means total mobility. Then we estimate share of offered mobility for each main mode of motorized transport (in CR conditions we speak about bus, railway and individual car passenger transport). These estimations are conducted overall for whole country or region and there are made scenario sensitivities form changes of the most important or uncertain presumptions. Generally mobility development models are projected to make possible formularization e.g. aggregate (regional or national) and long-term scenario. In essence we work on transport planning tradition and model explains, how passengers can select particular transport modes by satisfying their demand for mobility (term “mobility” used in model represents traffic volume measured by personal kilometres). But this model requires aggregated data. The aim of this model is not calculation of detailed estimations of travel distances and vehicles speeds, but rather total mobility prediction and prediction of offered share of each transport mode (so called modal split) within state and in aggregated regions in distant future. Future mobility development is determined by specific values of each transport mode in certain region or state. Within global mobility air transport share will increase in future, but other transport modes shares will decrease. In case of regional prognosis it is estimated that traffic volume share operated by conventional railways and HST has identical development in all world regions. However this uniform trend is estimated in no scenarios of cars and buses, although transparent trends are evident for these transport modes in majority of regions. In compliance with mobility future development slower transport modes will be substituted by faster. On permanently higher mobility levels then car share decreases according to growth of faster transport modes need (especially air transport) for satisfaction of increasing demand for mobility within fixed travel time budget. Multiple growth in mobility per capita cause demands of extreme mobility which proves by more frequent commuting for longer distances from place of living. Because extreme mobility depends on approach to high-speed transport modes, sparse inhabited areas will remain in certain regions. It relates to areas where travelling to traffic junctions (airports and stations of high-speed trains) is time demanding in HST system. By means of traffic volume prediction (car, bus, railway and high-speed transport, especially air and railway), the number of travels is estimated in distant future, used transport modes, e.g. within EU, in particular state or regions. Answers of these questions are decisive for long-term transport infrastructure planning and for mobility impacts assessment e.g. on environment. These matters are also the centre of interest by future market extension estimating for transport services technical equipment. We make efforts to create simple, but radical model, which shows probable answers of these questions. Reply of these questions requires construction of large-scale long-term models of transport system. But this mobility need very sharply contrasts with capacities of existing modeling techniques. Regional and urban transport models, which are the most intensive developed tools of transport planning must be orientated to prediction of local transport demand, flows and costs. These instruments optimalize direct traffic flows by cost minimization or consumer (passenger) utility maximization. They calculate with transport system details like e.g. numbers of cars using roads during several times and average speeds of location of lately built-up transport infrastructure. Essential detailed effect is also the fact that these models are based on big mutually related variables as car ownership, loading and vehicles utilization, travel banded charges, transport modes relative prices, urban travel speeds and passengers income. Regarding insufficient knowledges of relations among these variables, these multi-variation methods quickly degrade in distant future plans. Original requirements of transport planning models make these methods more inadequate tools for long-term scenarios development.
Vývoj budoucí mobility v osobní dopravě
Keywords: mobilita; osobní doprava; modely vývoje mobility; budoucnost